FIRE RETARDANTS - Nazarov Feruz Farxodovich (Web of Journals Publishing, 2024)
As is known, all resinous polymers are flammable. Therefore, in order for polymer materials to meet fire safety requirements, flame retardants (fire retardants) are added to their composition. Additives must also meet high fire safety requirements.
Keywords: Here are the main areas of application of fire retardants: electrical and electronic devices, for example, television components, fuses, switches, plugs, etc.